Canva-Based Educational Game Media Containing Local Wisdom to Improve Elementary School Students' IPAS Conceptual Skills - Ni Made Dwijayanti; I Gede Suwindia; I Nyoman Raka (LPPM Undiksha, 2026)
Elementary school students' understanding of science concepts remains relatively low because less engaging, less interactive media often dominate learning. In addition, the learning media used are not contextual and do not link the material to local wisdom in the students' surroundings. This study aims to analyze the effectiveness of Canva-based educational game media containing local wisdom on the science concept abilities of fifth-grade elementary school students. The study used a quantitative approach with a One-Group Pretest-Posttest design, involving 31 students as subjects. Data were collected through conceptual ability tests given before and after the media application. Data analysis was carried out using descriptive and inferential statistics, with the prerequisite of normality tests using the Kolmogorov-Smirnov test and homogeneity-of-variance tests, as well as hypothesis testing using the Paired Sample t-Test in SPSS version 29.0. The test results showed a significant increase in conceptual abilities, with a calculated t-value t p < 0.001, indicating a difference in students' conceptual abilities before and after treatment. The conclusion of this study shows that Canva-based educational game media incorporating local wisdom is effective in improving students' understanding of science concepts. At the same time, the implications indicate that this media can present science material interactively, contextually, and relevant to local culture, thereby supporting the achievement of learning objectives.